Cyclopent-2-enylaluminium as allylzinc precursor for the diastereoselective allylmetallation of non-racemic imines: applications to the synthesis of enantiomerically enriched heterocycles. Issue 1 (13th November 2015) - Coffinet, Michaël; Lamy, Samantha; Jaroschik, Florian; Vasse, Jean-Luc
Abstract : A sequential titanium-catalyzed/hydroalumination/transmetallation/allylation of non-racemic imines which provides tunable homoallylamines for heterocyclic synthesis is presented. Abstract : The generation of cyclopent-2-enylzinc from cyclopentadiene based on a titanium-catalyzed hydroalumination/transmetallation sequence is described. Applied to the allylmetallation of phenylglycinol-derived imines, this sequence leads to homoallylic amines with moderate to good stereoselectivities. The synthesis of disubstituted azetidines and piperidines illustrates the potential of the method.